TARIX FANIDAN OʻQUV TOPSHIRIQLARI TUZISHGA PRAGMATIK YONDASHISH - Rzambetova, G.A. (SCIENCE and SOCIETY, 2024)
The article describes the development of pragmatic learning tasks for history lessons, the development of skills for composing targeted questions and tasks, the formation of learning tasks that form students’ independent thinking, able to work independently with data, compare data and highlight the necessary moments from them, the most important in history, can highlight the necessary information and topics for the student.